PEMANFAATAN DAN POTENSI ENERGI LISTRIK DARI LIMBAH PADAT DAN CAIR PROSES PENGOLAHAN KELAPA SAWIT - Panjaitan, Bintang Sipartogi; Tambunan, Armansyah Halomoan (Program Studi Teknik Pertanian, Fakultas Pertanian, Universitas Jenderal Soedirman, 2025)
The palm oil production process yields crude palm oil (CPO) and palm kernel as its main products, along with byproducts such as empty fruit bunches (EFB), fiber, palm kernel shells, and palm oil mill effluent (POME). This study aims to analyze waste utilization and estimate the potential electrical energy that can be generated from these solid and liquid wastes at PT X. The analysis involves observation, measurement, data collection, and calculations based on mass balance principles. At PT X, EFB is incinerated, while fiber and shells are utilized as boiler fuel. POME is treated in open lagoons and used as liquid fertilizer for company-owned plantations. Based on daily operational data and calorific values, the estimated potential energy is 18,174,559.55 MJ from EFB, 7,538,070.26 MJ from palm kernel shells, and 2,125,525.40 MJ from biogas. With an operational time of 720 hours per month, PT X has the potential to generate 2.63 MW of electricity. The findings highlight the significant energy potential of palm oil waste. Therefore, further development of waste processing technologies is essential to maximize energy recovery, support internal energy needs, and potentially supply electricity to surrounding areas.